QoS Performance Analysis of Bit Rate Video Streaming in Next Generation Networks Using TCP, UDP and a TCP+UDP Hybrid - Dlamini, Xolani; Lugayizi, Francis L.; Esiefarienrhe, Bukohwo M. (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2016)
The growth in users streaming videos on the Internet has led to increased demand for improved video quality and reception. In next generation networks (NGNs), such as 3G and 4G LTE, quality of service (QoS) implementation is one of the ways in which good video quality and good video reception can be achieved. QoS mainly involves following an industry-wide set of standard metrics and mechanisms to achieve high-quality network performance in respect of video streaming. Adopting routing and communication protocols is one way QoS is implemented in NGNs. This article describes QoS of bit rate video streaming, and QoS performance analysis of video streaming, in relation to the main network transport protocols, namely transmission control protocol (TCP) and user datagram protocol (UDP). A simulation test bed was set up using OPNET modeller 14.5. In this setup, a network topology was created and duplicated three times, in order to configure two simulation scenarios (each using the distinct protocols), and a third simulation scenario using both protocols in hybrid form. The findings in the simulations indicated that, when a network is configured with both TCP and UDP protocols in video streaming, there is a positive change in the degree of performance in terms of the QoS of videostreaming applications, unlike when the protocols are used independently.
Keywords: quality of service, QoS, bit rate, video streaming, QoS routing, TCP, UDP